Antonio Benítez Rojo : del mundo cerrado al Caribe infinito - Corticelli, María Rita, 1966- (Colección Támesis. Monografías, 2013)
The author of short stories, novels and essays, Benítez Rojo is an atypical intellectual in the panorama of Cuban exile because he offers an original perspective of the past, present and future conflicts of this troubled and complex area. This literary biography tells of his journey from his emergence in the Cuban intellectual world in 1967 to his death in Amherst, Massachusetts, in 2005.